IMPLEMENTASI "SEKOLAH SAK NGAJINE" DALAM MEMBENTUK KARAKTER SISWA BERAKHLAKUL KARIMAH DI SMA DHARMA WANITA 01 BULULAWANG - Adi Cahyono; Yazidul Busthomi (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
The implementation of the “Sak Ngajine” concept in shaping students' character with good morals at SMA Dharma Wanita 01 Bululawang is based on several fundamental aspects, including the school's vision, cooperation with Islamic boarding schools, the diverse backgrounds of students, and references from the Qur'an and Hadith. This study used a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation involving the principal, teachers, and others. The results of the study show that this program has led to an increase in students' religious attitudes, discipline, and social awareness. Structured religious activities contribute to the development of students' morals, time management, and responsibility. However, this program faces challenges such as differences in religious understanding among students and the influence of the environment outside of school. Nevertheless, strong institutional support and adequate facilities play a significant role in the success of this program.